2010
DOI: 10.1111/j.1440-1843.2009.01703.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in non‐small cell lung cancer patients after chemotherapy: Association with treatment response

Abstract: In lung cancer patients, oxidative stress increased and anti-oxidant enzymes decreased as the disease progressed. Chemotherapy may suppress oxidative stress and decreased anti-oxidant enzyme activity in responders as compared with non-responders. These effects may contribute to improved survival among responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 49 publications
(98 reference statements)
1
63
0
3
Order By: Relevance
“…In line with this, it has also been well established that patients with underlying respiratory conditions such as chronic obstructive pulmonary disease (COPD), which also represents a major cause of morbidity and mortality in developed countries, exhibit a significantly greater risk of LC (3,(10)(11)(12)(13)(14)(15)(16)(17). Importantly, in patients with moderate-to-severe COPD, the prevalence of LC can go up as high as five-fold that of smokers without the disease (18)(19)(20)(21)(22)(23)(24). Furthermore, the epidemiologic relevance of emphysema in the development of LC in patients with COPD has also been highlighted (2)(3)(4)(5)16).…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…In line with this, it has also been well established that patients with underlying respiratory conditions such as chronic obstructive pulmonary disease (COPD), which also represents a major cause of morbidity and mortality in developed countries, exhibit a significantly greater risk of LC (3,(10)(11)(12)(13)(14)(15)(16)(17). Importantly, in patients with moderate-to-severe COPD, the prevalence of LC can go up as high as five-fold that of smokers without the disease (18)(19)(20)(21)(22)(23)(24). Furthermore, the epidemiologic relevance of emphysema in the development of LC in patients with COPD has also been highlighted (2)(3)(4)(5)16).…”
Section: Introductionmentioning
confidence: 62%
“…More recently, patients with advanced LC exhibited increased systemic oxidative stress levels compared to healthy controls (18,33). In a previous study from our group (25), protein carbonylation levels, as measured by malondialdehyde (MDA)-protein adducts, were also increased in the normal epithelium of patients with LC, especially in patients with underlying COPD, whose levels were significantly greater than in those without this disease.…”
Section: Redox Balancementioning
confidence: 88%
See 2 more Smart Citations
“…Subsequently, oxidized substances such MDA is formed. Parallel to this, increased oxidative stress and decreased antioxidant enzymes have been observed in lung cancer patients as the disease progresses (Gupta et al 2010). Schramm et al (2003) reported that natural honey contains numerous antioxidant compounds that delay, prevent or remove oxidative damages (Erejuwa et al 2012).…”
Section: Discussionmentioning
confidence: 99%